Financial Planning Daksa Medical Laboratory Business Development Project - El Khair, Minanda; Rahmat Syah, Tantri Yanuar; Indradewa, Rhian; Sunaryanto, Ketut (Action Research Literate, 2024)
Effective financial planning and careful analysis of financial ratios are essential in the development of a medical laboratory business plan.  Medical laboratories play a crucial role in the healthcare industry by providing vital diagnostic services. However, financial challenges such as the procurement of sophisticated equipment and high operational costs are often obstacles.  This study evaluated the financial planning for the business development project of Daksa Medical Laboratory in South Tambun, Bekasi Regency. Through descriptive qualitative methods, financial planning includes financial objectives, capital structure, investments, financing, and financial projections. Financial ratio analysis is integrated into a business plan to evaluate the financial health of the laboratory. The results showed that this financial planning shows the growth potential and investment feasibility for Daksa Medical Laboratory.